Acute consumption of varied doses of cocoa flavanols does not influence exercise-induced muscle damage - Corr, L. D.; Field, A.; Pufal, D.; Killey, J.; Clifford, T.; Harper, L. D.; Naughton, R. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Polyphenol consumption has become a popular method of trying to temper muscle damage. Cocoa flavanols (CF) have attracted attention due to their high polyphenol content and palatability. As such, this study will investigate whether an acute dose of CF can aid recovery following exercise-induced muscle damage. The study was a laboratory-based, randomized, single-blind, nutrient-controlled trial involving 23 participants (13 females and 10 males). Participants were randomized into either control ~0 mg CF (n = 8, four females); high dose of 830 mg CF (CF830, n = 8, five females); or supra dose of 1,245 mg CF (CF1245, n = 7, four females). The exercise-induced muscle damage protocol consisted of five sets of 10 maximal concentric/eccentric hamstring curls and immediately consumed their assigned drink following completion. To measure muscle recovery, maximal voluntary isometric contraction (MVIC) of the knee flexors at 60° and 30°, a visual analog scale (VAS), and lower-extremity function scale were taken at baseline, immediately, 24-, 48-, and 72-hr postexercise-induced muscle damage. There was a main effect for time for all variables (p < .05). However, no significant differences were observed between groups for all measures (p = .17). At 48 hr, there were large effect sizes between control and CF1245 for MVIC60 (p = .17, d = 0.8); MVIC30 (p = .26, d = 0.8); MVIC30 percentage change (p = .24 d = 0.9); and visual analog scale (p = .25, d = 0.9). As no significant differences were observed following the consumption of CF, there is reason to believe that CF offer no benefit for muscle recovery when ingested acutely.